The girls' guide to hunting and fishing - Bank, Melissa (New York, N.Y., U.S.A. : Penguin Books, 2000)
Seven stories on a woman's search for love, first as a defiant teenager and finally as a reluctant career girl. The heroine narrates, "There are stacks and stacks of How to Meet and Marry Mr. Right, and I take my copy up to the counter as furtively as if it were a girdle or vibrator."
Advanced beginners -- The floating house -- My old man -- The best possible light -- The worst thing a suburban girl could imagine -- You could be alone -- The girls' guide to hunting and fishing.
Originally published: New York, N.Y. : Viking, 1999.
Keywords: Man-woman relationships -- United States -- Fiction; Young women -- United States -- Fiction; Love stories, American; United States -- Social life and customs -- 20th century -- Fiction